Computational modeling of cracking in autoclaved aerated concrete blocks and masonry wallets. - Fernández-Baqueiro, Luis; Ceballos-Pérez, Laura; Moreno-Herrera, Joel; Varela-Rivera, Jorge (Revista ALCONPAT, 2025)
The objective of this research was to study the cracking process of autoclaved aerated concrete (AAC) blocks and masonry wallets with discrete crack models of the Finite Element Method. The results of an experimental study were analyzed to develop computational models. Models of the splitting tensile strength tests of blocks and the diagonal tensile strength test of masonry wallets, of different sizes, were developed. Rankine and Mohr failure criteria were considered for the interface elements. The cracking loads were determined. It was concluded that, with the developed models, the cracking loads and the failure mechanism of AAC blocks and wallets are well simulated compared to what was observed experimentally.